2000
DOI: 10.2307/3284925
|View full text |Cite
|
Sign up to set email alerts
|

Randomly Amplified Polymorphic DNA (RAPD) Polymerase Chain Reaction Assay for Identification of Schistosoma mansoni Strains Sensitive or Tolerant to Anti-Schistosomal Drugs

Abstract: The genetic differences between Schistosoma mansoni strains from different geographic areas that were reportedly resistant or sensitive to anti-schistosomal drugs were studied with randomly amplified polymorphic DNA (RAPD) and simple sequence repeat (SSR) polymerase chain reaction (PCR) assays. Of the 20 RAPD primers we chose, 19 showed the capacity to produce a medium to high level of amplification and 6 revealed difference PCR bands between drug-resistant and drug-sensitive strains. One particular primer, 5'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In one study, two major DNA nucleotide sequence differences were found between an Egyptian PZQresistant isolate and several PZQ-sensitive isolates from the same endemic area (Tsai et al 2000). In the second study, subtractive PCR showed a PZQsensitive and a PZQ-resistant isolate to be different in the expression and activity of the mitochondrial enzyme cytochrome C-oxidase (Pereira et al 1998).…”
Section: Mechanisms Of Action Of Pzq and Markers Of Resistancementioning
confidence: 99%
“…In one study, two major DNA nucleotide sequence differences were found between an Egyptian PZQresistant isolate and several PZQ-sensitive isolates from the same endemic area (Tsai et al 2000). In the second study, subtractive PCR showed a PZQsensitive and a PZQ-resistant isolate to be different in the expression and activity of the mitochondrial enzyme cytochrome C-oxidase (Pereira et al 1998).…”
Section: Mechanisms Of Action Of Pzq and Markers Of Resistancementioning
confidence: 99%
“…Also, they presented different band polymorphism patterns with monomorphic bands of similar molecular weights. RAPD-PCR was found to be a rapid and low-cost technique for identification of polymorphic bands representing DNA amplification extracted from different stages of the S. mansoni development cycle exposed to different periods of in vivo treatments [40] .…”
Section: Dendrogram Using Average Linkage (Between Groups)mentioning
confidence: 99%
“…(1998) described an RT–PCR which allows to identify an overexpression of a fragment of subunit 1 of cytochrome‐c oxidase in resistant strains. Recently, Tsai et al . (2000) discovered a primer for RAPD–PCR which was able to distinguish resistant from sensitive Egyptian strains of S. mansoni .…”
Section: Detection Of Drug Resistancementioning
confidence: 99%